PEMANFAATAN APLIKASI SIMULASI RANGKAIAN LISTRIK SEBAGAI MEDIA PEMBELAJARAN FISIKA - Ade Silvia Handayani; Nyayu Latifah Husni; Rumiasih Rumiasih; Carlos R Sitompul; Sopian Soim; Ali Nurdin; Jon Endri; Suroso Suroso; Nurhaida Nurhaida (Politeknik Negeri Sriwijaya, 2020)
Physics is a subject that delve into natural phenomena on the environment. Students on Junior High School until Senior High School starts to learn physics. It is due to physics is related to natural phenomena, it does not only contain theory but also calculation and practice. One of the subjects that can be learnt in physics is Electrical Circuits. To learn more about physics, we need to understand the theory and also the basic calculation in order to implement it in the real situation. However, the main problem is people are not interested to learn those things from a book, and people need to pay more for the practical things. This may be a problem because some of the practical things cannot be found easily. Therefore, to solve the problems, giving a workshop about Livewire is a perfect solution. This workshop will give people to stake out easier with Liverwire application. In addition, Livewire provides us to know the flow or the voltage on our own channel. To attract the students and to get the best study results, Livewire is ready to be friends with Physics teachers.